Do physical maturity and birth date predict talent in male youth ice hockey players? - Sherar, L. B.; Baxter-Jones, A. D. G.; Faulkner, R. A.; Russell, K. W. (Journal of Sports Sciences, 2007)
The aim of this study was to examine the relationships among biological maturity, physical size, relative age (i.e. birth date), and selection into a male Canadian provincial age-banded ice hockey team. In 2003, 619 male ice hockey players aged 14 - 15 years attended Saskatchewan provincial team selection camps, 281 of whom participated in the present study. Data from 93 age-matched controls were obtained from the Saskatchewan Pediatric Bone Mineral Accrual Study (1991 - 1997). During the initial selection camps, birth dates, heights, sitting heights, and body masses were recorded. Age at peak height velocity, an indicator of biological maturity, was determined in the controls and predicted in the ice hockey players. Data were analysed using one-way analysis of variance, logistic regression, and a Kolmogorov-Smirnov test. The ice hockey players selected for the final team were taller, heavier, and more mature (P < 0.05) than both the unselected players and the age-matched controls. Furthermore, age at peak height velocity predicted (P < 0.05) being selected at the first and second selection camps. The birth dates of those players selected for the team were positively skewed, with the majority of those selected being born in the months January to June. In conclusion, team selectors appear to preferentially select early maturing male ice hockey players who have birth dates early in the selection year.